2016
DOI: 10.15713/ins.jmrps.58
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of oral cancer among medical students in Chennai

Abstract: Background: Most common cause of death in developed and developing countries is oral cancer, with increasing habits of smoking, tobacco chewing, and alcohol consumption. Early diagnosis required for better cure rates and improves the quality of life. Screening of oral cancer in general hospitals provides a "window of opportunity" for early diagnosis. Aim: To assess the knowledge of oral cancer and the screening practice among medical students in Chennai city. Objective: To investigate whether medical students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…Therefore the student should be trained well enough to make the note of these changes and make early referrals which can be life saving for the patients also 2 . The study was conducted with the aim of assessing the level of competency of the upcoming health care professionals in regard to diagnosing, preventing and referring patients with a risk of oral cancer [3][4][5][6][7] . The survey included 100 dental and medical undergraduates from third and final year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore the student should be trained well enough to make the note of these changes and make early referrals which can be life saving for the patients also 2 . The study was conducted with the aim of assessing the level of competency of the upcoming health care professionals in regard to diagnosing, preventing and referring patients with a risk of oral cancer [3][4][5][6][7] . The survey included 100 dental and medical undergraduates from third and final year.…”
Section: Discussionmentioning
confidence: 99%
“…This responsibility lies in the hands of the practitioners to detect early oral changes and make referrals to specialists as and when required 2 . For this the budding medical and dental professionals should be trained properly to carry out routine diagnostic procedures without missing out the suspicious cases 3 . Also the health care professional should be competent enough to judge the patients at high risk from their history and make intelligent referrals as and when needed 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the occurrence of the tongue and buccal mucosa cancer has been increased in India with a higher number of buccal mucosa cancer cases [ 11 ]. A group from Chennai reported that oral cancer is most prevalent at the base of the tongue and the base of the mouth that enhances the metastasis [ 12 ]. Another group has reported that buccal mucosa, alveolus, and the base of the mouth are the most prevalent sites for the occurrence of oral cancer [ 13 ].…”
Section: Status Of Oral Cancer In Indiamentioning
confidence: 99%
“…Beyond prevention, early detection is the most crucial determinant for successful treatment and better prognosis. [1][2][3] The early progression and metastasis reduces the 5-year survival rate to 50%. 4 The incidence of metastasis depends on the degree of cellular differentiation, deep invasion, and site of the primary tumor.…”
Section: Introductionmentioning
confidence: 99%